Prospects for the use of BIM in Poland and the Czech Republic – Preliminary Research Result - Juszczyk, Michał; Výskala, Miloslav; Zima, Krzysztof (Elsevier, 2015)
The building information modelling (BIM) has received increased attention in the construction sector. BIM is becoming a widespread and common approach in the design, construction and maintenance of building facilities. BIM is also one the most widely discussed topics both by the academics and professionals from the construction industry all over the world. The purpose of this article is to present the initial results of studies on the use of BIM in construction projects in Poland and the Czech Republic. The studies cover a widely understood field of management in construction projects. Research concerns the scale of the use of BIM in the construction project management, the awareness of the BIM possibilities and a potential for the participants of construction projects. In the paper the authors discuss the results of the studies and compare the situation in Poland and the Czech Republic

The building information modelling (BIM) has received increased attention in the construction sector. BIM is becoming a widespread and common approach in the design, construction and maintenance of building facilities. BIM is also one the most widely discussed topics both by the academics and professionals from the construction industry all over the world. The purpose of this article is to present the initial results of studies on the use of BIM in construction projects in Poland and the Czech Republic. The studies cover a widely understood field of management in construction projects. Research concerns the scale of the use of BIM in the construction project management, the awareness of the BIM possibilities and a potential for the participants of construction projects. In the paper the authors discuss the results of the studies and compare the situation in Poland and the Czech Republic
Prospects for the use of BIM in Poland and the Czech Republic – Preliminary Research Result
Keywords: Building Information Modelling; BIM software; BIM tools; construction management; Building Information Modelling; BIM software; BIM tools; construction management